Still unconvinced, but still tentative: a reply to DeGrazia. Issue 3 (2nd December 2011) - Buchanan, Allen
Abstract : David DeGrazia's article provides a careful and fair rendition of my position on the possibility of post-persons. However, I am unconvinced that he has shown that such beings are possible. My view is based on two assumptions: (1) the concept of moral status is a threshold concept; and (2) the most plausible understanding of moral status as a threshold concept is a Kantian respect-based view, according to which all and only those beings who have the capacity to be accountable for reasons have the high status we associate with persons. I argue that the superior beings DeGrazia describes would be more morally admirable than us, but would not have a higher moral status. I also argue that, contrary to DeGrazia, even the most intelligent of canines do not have the capacity for accountability for reasons, even in an attenuated form. I then argue that DeGrazia faces a painful dilemma: either he must give up the assumption that moral status (so far as persons are concerned) is a threshold concept and say that for any two beings with the capacity for accountability for reasons, the one with the greater capacity has a higher moral status; or he must retain the view that moral status is a threshold concept but concede that he has not account of where the threshold lies.